Subcutaneous Injection of Nitroglycerin at the Radial Artery Puncture Site Reduces the Risk of Early Radial Artery Occlusion After Transradial Coronary Catheterization: A Randomized, Placebo-Controlled Clinical Trial. (July 2018) - Chen, Yequn; Ke, Zhiquan; Xiao, Jiaxin; Lin, Mengyue; Huang, Xiru; Yan, Chunyin; Ye, Shu; Tan, Xuerui
Abstract : Background: Transradial coronary catheterization is widely used as a diagnostic or interventional procedure for coronary disease. However, it can lead to adverse complications, such as radial artery occlusion. We sought to determine whether preprocedural injection of nitroglycerin at the radial artery puncture site reduces radial artery occlusion. Methods and Results: A total of 188 patients undergoing transradial coronary catheterization were randomized in a single-blind fashion to receive subcutaneous injection of 0.5 mL 0.1% nitroglycerin or a placebo at the radial artery puncture site. The participants underwent ultrasound examinations of the radial artery before and at 24 hours after the procedure. Of the 188 patients enrolled, 182 completed the study, as the procedure failed in 2 participants in the nitroglycerin-treated group and 4 in the placebo group. Baseline demographic and clinical characteristics were similar between 2 groups. Comparing the radial artery diameters before and after the operation, there was a statistically significant increase in the nitroglycerin-treated group (2.48±0.45 versus 2.45±0.46 mm; P =0.003) but a decrease in the placebo control group (2.41±0.50 versus 2.46±0.49 mm; P <0.001). Importantly, the incidence of radial arterial occlusion was substantially lower in the nitroglycerin-treated group than in the placebo control group (5.4% versus 14.4%; P =0.04). There was not significant difference in other complications (forearm hematoma and radial artery pseudoaneurysm, respectively), and there was no incidence of cause hypotension or an intolerable headache. Conclusions: Subcutaneous injection of nitroglycerin at the radial artery puncture site dilates the radial artery and reduces the incidence of early radial artery occlusion post-catheterization. Clinical Trial Registration: URL:https://www.chictr.org.cn . Unique identifier: ChiCTR-IPR-15006559.